2015
DOI: 10.15580/gjas.2015.1.011515003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Access to Formal Credit by Smallholder Tobacco Farmers in Makoni District, Zimbabwe

Abstract: This study used data from 77 smallholder tobacco farmers from Makoni district in Zimbabwe to investigate factors affecting smallholder tobacco farmers' access to formal credit. The results of the study showed that contact with extension services, farmer's attitude towards risk of borrowing and ownership of land cultivated significantly and positively influenced the probability of farmers' access to formal credit in the study area. These findings confirm that improving access to extension services and secure la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
5
16
1
Order By: Relevance
“…Similar findings were obtained in Ghana, where the fear of loan default was the most important reason that prevented farmers from participating in agricultural credit programs (Asante-Addo et al, 2017). In Zimbabwe, Dube et al (2015) also established that the majority (63%) of farmers not accessing formal credit feared taking the risk that came with borrowing.…”
Section: Fear Of Debt (Fod)supporting
confidence: 72%
See 1 more Smart Citation
“…Similar findings were obtained in Ghana, where the fear of loan default was the most important reason that prevented farmers from participating in agricultural credit programs (Asante-Addo et al, 2017). In Zimbabwe, Dube et al (2015) also established that the majority (63%) of farmers not accessing formal credit feared taking the risk that came with borrowing.…”
Section: Fear Of Debt (Fod)supporting
confidence: 72%
“…Chitungo and Munongo (2015) investigated the effect of various farmer and farm characteristics (age, marital status, education, household size, income, remittances, and crop type) on the farmers' decision to apply for credit from informal lenders in the rural districts of Zaka, Chiredzi and Masvingo. Dube et al (2015) only focused on the determinants of credit access in the formal sector among smallholder tobacco farmers in Makoni District. Therefore, no study to the researcher's knowledge has applied the DEA to comprehend how lender/ supply side attributes affect Zimbabwean farmers' credit demand for bank credit.…”
Section: Introductionmentioning
confidence: 99%
“…Using a linear regression analysis to demonstrate the linkage between various socioeconomic characteristics of the farmers and their rate of accessibility to the agricultural credit, Etonihu et al (2013) reported that the formal education, distance to formal financial institutions and types of credit source were significant factors prompting smallholders' accessibility to credit in Nigeria. Determinants of access to formal credit by smallholder tobacco farmers in Makoni District, Zimbabwe, were investigated by Dube et al (2015) by utilizing survey data of 77 smallholder tobacco farmers. The results of logit regression model revealed that improved access to credit usage information by extension programs is expected to have a significant effect on the attitudes of farmers about credit risk, which in turn will reduce the concerns associated with structured credit sources.…”
Section: Agricultural Credit Demand In Pakistanmentioning
confidence: 99%
“…Formal agricultural credit is an important farm input along with modern technology playing role for improved crops yield and accelerating agricultural modernization and economic development (Anang et al, 2015). According to Dube et al (2015) and Zeller et al's (1997) studies, the welfare of households is affected by access to credit and eliminating the capital constraints during the vegetation growth and planting season of crops, thereby increasing the capabilities of those with low or no savings to meet their financial needs for crop production. The formal agricultural loan is not required only for the small-and medium-scale farmers for survival, but also large-scale farmers can get benefit to improve farm income with minimal savings (Das et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation